Structure, function, and immunomodulation of the CD8 co-receptor - Srinivasan, Shreyaa; Zhu, Cheng; McShan, Andrew C. (Frontiers in Immunology, 2024)
Expressed on the surface of CD8 + T cells, the CD8 co-receptor is a key component of the T cells that contributes to antigen recognition, immune cell maturation, and immune cell signaling. While CD8 is widely recognized as a co-stimulatory molecule for conventional CD8 + αβ T cells, recent reports highlight its multifaceted role in both adaptive and innate immune responses. In this review, we discuss the utility of CD8 in relation to its immunomodulatory properties. We outline the unique structure and function of different CD8 domains (ectodomain, hinge, transmembrane, cytoplasmic tail) in the context of the distinct properties of CD8αα homodimers and CD8αβ heterodimers. We discuss CD8 features commonly used to construct chimeric antigen receptors for immunotherapy. We describe the molecular interactions of CD8 with classical MHC-I, nonclassical MHCs, and Lck partners involved in T cell signaling. Engineered and naturally occurring CD8 mutations that alter immune responses are discussed. The applications of anti-CD8 monoclonal antibodies (mABs) that target CD8 are summarized. Finally, we examine the unique structure and function of several CD8/mAB complexes. Collectively, these findings reveal the promising immunomodulatory properties of CD8 and CD8 binding partners, not only to uncover basic immune system function, but will advance efforts towards translational research for targeted immunotherapy.